Infertility control of transgenic fluorescent zebrafish with targeted mutagenesis of the dnd1 gene by CRISPR/Cas9 genome editing - Chu, Wai-Kwan; Huang, Shih-Chin; Chang, Ching-Fong; Wu, Jen-Leih; Gong, Hong-Yi (Frontiers in Genetics, 2023)
Transgenic technology and selective breeding have great potential for the genetic breeding in both edible fish and ornamental fish. The development of infertility control technologies in transgenic fish and farmed fish is the critical issue to prevent the gene flow with wild relatives. In this study, we report the genome editing of the dead end (dnd1) gene in the zebrafish model, using the CRISPR/Cas9 technology to achieve a loss-of-function mutation in both wild-type zebrafish and transgenic fluorescent zebrafish to develop complete infertility control technology of farmed fish and transgenic fish. We effectively performed targeted mutagenesis in the dnd1 gene of zebrafish with a single gRNA, which resulted in a small deletion (-7 bp) or insertion (+41 bp) in exon 2, leading to a null mutation. Heterozygotes and homozygotes of dnd1-knockout zebrafish were both selected by genotyping in the F_1 and F_2 generations. Based on a comparison of histological sections of the gonads between wild-type, heterozygous, and homozygous dnd1 zebrafish mutants, the dnd1 homozygous mutation (aa) resulted in the loss of germ cells. Still, there was no difference between the wild-type (AA) and dnd1 heterozygous (Aa) zebrafish. The homozygous dnd1 mutants of adult zebrafish and transgenic fluorescent zebrafish became all male, which had normal courtship behavior to induce wild-type female zebrafish spawning. However, they both had no sperm to fertilize the spawned eggs from wild-type females. Thus, all the unfertilized eggs died within 10 hours. The targeted mutagenesis of the dnd1 gene using the CRISPR/Cas9 technology is stably heritable by crossing of fertile heterozygous mutants to obtain sterile homozygous mutants. It can be applied in the infertility control of transgenic fluorescent fish and genetically improved farmed fish by selective breeding to promote ecologically responsible aquaculture.